Zn–Air Batteries: Web‐Like Interconnected Carbon Networks from NaCl‐Assisted Pyrolysis of ZIF‐8 for Highly Efficient Oxygen Reduction Catalysis (Small 16/2018). Issue 16 (19th April 2018) - Qian, Yuhong; An, Tao; Birgersson, Karl Erik; Liu, Zhaolin; Zhao, Dan
Abstract : In article number1704169, Dan Zhao and co‐workers propose a method to prepare hierarchical interconnected carbon networks with ultrahigh pore volume from NaCl/ZIF‐8 composites. The carbon networks exhibit outstanding activity, kinetics, and stability towards catalyzing the oxygen reduction reaction. They can be further integrated into cathodes of Zn–air batteries to achieve a triple life‐hour compared with Pt/C cathodes.